On the Role of Amides and Imides for Understanding GaN Syntheses from Ammonia Solution: Molecular Mechanics Models of Ammonia, Amide and Imide Interactions with Gallium Nitride - Wonglakhon, Tanakorn; Zahn, Dirk (ChemPhysChem, 2022)
A key requisite to characterizing GaN precipitation from ammonia solution from molecular simulations is the availability of reliable molecular mechanics models for the interactions of gallium ions with NH3, NH2-, and NH2- species, respectively. Here, we present a tailor-made force field which is fully compatible to an earlier developed GaN model, thus bridging the analyses of Ga3+ ions in ammonia solution with the aggregation of [Ga-x(NH)(y)(NH2)(z)](+3x-2y-z) precursors and the modelling of GaN crystals. For this, quantum mechanical characterization of a series of Ga-coordination clusters is used for parameterization and benchmarking the generalized amber force field (GAFF2) and tailor-made refinements needed to achieve good agreement of both structural features and formation energy, respectively. The perspectives of our models for larger scale molecular dynamics simulations are demonstrated by the analyses of amide and imide defects arrangement during the growth of GaN crystal faces.
CRIS-Team WoS Importer:2022-06-03